The Influence of Transformational Leadership, Organizational Commitment, Management Support on Innovation Performance in Insurance Companies - Omdali Putri, Aulia Sindiyeni; Rahadi, Bayu; Hartono, Edy (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: The following study aims to explore the influence of transformational leadership, organizational commitment, and management support on innovation performance in insurance companies in Indonesia. Methodology: The following study employed a quantitative methodology, utilizing a survey as the tool for data collection. Data was collected by administering surveys to staff members of 4 insurance companies in Cirebon City. The SPSS software was used to enable multiple linear regression in the data analysis process. Findings: The following research results prove that transformational leadership (X1), organizational commitment (X2), and management support (X3) have a positive and significant influence on innovation performance (Y) in insurance companies. This finding confirms the importance of creating effective transformational leadership, increasing organizational commitment, and providing optimal management support to encourage increased innovation performance in the insurance sector. Improving these three factors contributes significantly, encouraging employees to be more active in innovating, and improving overall company performance. The analysis proves that transformational leadership has a regression coefficient of 0.279, while organizational commitment reaches 0.536, and management support is 0.131. This underscores that these three factors are key to driving innovation. Originality/value: This paper is original Paper type: a Research Paper